The Poetics of T. S. Eliot and Salah Abdel-Sabour: A Thematic-Mythical Intertextuality - Abdullah Kurraz (My University, 2011)
The paper explores the similarities and parallels between the poetics of both T.S. Eliot and Salah Abdel-Sabour on the thematic use of mythical allusions and objective correlatives. Both poets show common human thematic interests and concerns of modern life, its predicaments and aspirations, mainly through evoking a web of such mythical allusions or mythopoetics. Based on Eliot's mythical method (mythopoetics) and his notion of objective correlatives, Abdel-Sabour reflects on the concept of intertextuality. The paper also traces the engagement of both poets in a process of trans¬cultural poetic dialogues. It argues that modern Arab poets, like Abdel-Sabour, attempt to construct bridges with Western poetics, namely Eliot's. Influenced by Eliot, Abdel-Sabour integrates the traditional and modernized mythical allusions to express the human concerns of modern man, basically, after experiencing various crises, conflicts and dilemmas, like 1984 and 1967 wars. Modern Arabic poetry, similar to Eliot's, has become a more relevant and reliable medium of expression to explore modern man in the worldwide.

يهتم هذا البحث باستكشاف أوجه التشابه في شاعرية كلٍ من الشاعر الإنجليزي ت. س. إليوت والشاعر العربي المصري صلاح عبد الصبور، والمتعلقة بتوظيف الأساطير أو تلميحاتها الأسطورية والمعادلات الموضوعية توظيفاً ذا مغزى. يعرض كلٌّ من الشاعرين التقاطعات والاهتمامات الإنسانية الموضوعية في الحياة المعاصرة، في مآزقها وتطلعاتها من خلال استحضار مجموعة من الإشارات الأسطورية. ويجسد عبد الصبور مفهوم التناص، وذلك اعتماداً على أسلوبية إليوت في توظيف الأسطورة شعراً و فكرة المعادل الموضوعي. كما يتتبع البحث اهتمام الشاعرين في حوارات شاعرية ثقافية/حضارية، ويبرهن محاولة الشعراء العرب الحداثيين، أمثال عبد الصبور، بناء جسور مع الشاعرية الغربية، وتحديداً، شاعرية إليوت. وتأثراُ بالشاعر إليوت، فإن عبد الصبور يدمج بين التراث الشعري التقليدي والآخر الحداثي للتعبير عن الاهتمامات الإنسانية للإنسان المعاصر، خصوصاً، بعد أن شهد صراعات وأزمات ومآزق متنوعة مثل حربي 1948م و1967م. لقد أصبح الشعر العربي الحديث، وعلى غرار شاعرية إليوت، وسيلة أكثر ملاءمة وموثوقيةً لاستكناه الإنسان الحديث في جميع أنحاء العالم.
شاعرية النص عند ت. س. إليوت و صلاح عبد الصبور: التناص الموضوعاتي الأسطوري